Coulomb systems in one and two dimensions: Exact results (2021)
Soft matter often features charged units. These charges interact through Coulomb forces, the treatment of which is difficult due to their long-range nature. This thesis gives results for three many- body systems where every long-range interaction is included, without approximations. The document includes a longer summary in English